DEVELOPMENTS IN BANCASSURANCE - INDIAN LIFE INSURANCE INDUSTRY - Sharma, Keertiman (PEOPLE: International Journal of Social Sciences, 2017)
The opening of insurance sector in the year 2000 has paved the way for entry of private insurance companies in India. With this development, the life insurance industry has witnessed growth and increased competition. Bancassurance has become an important channel of distribution of the insurance products. This concept has its origins in France but has now become popular in different parts of the world. It is made up of two words – bank and assurance. Apart from the traditional and most common distribution channels like online distribution, agency, brokers and direct selling, bancassurance is seen by many as an important channel. Banks in India have a large network including in the remote areas. This has helped the Life insurance companies to get improved geographical reach. Through the development and effective use of this distribution channel, the Life insurance players have been able to target previously untapped markets. For the banks too, it has become an important source of income.